Seasonal shifts in isoprenoid emission composition from three hyperdominant tree species in central Amazonia. (31st March 2022) - Gomes Alves, E.; Taylor, T.; Robin, M.; Pinheiro Oliveira, D.; Schietti, J.; Duvoisin Júnior, S.; Zannoni, N.; Williams, J.; Hartmann, C.; Gonçalves, J. F. C.; Schöngart, J.; Wittmann, F.; et al.
Abstract: Volatile isoprenoids regulate plant performance and atmospheric processes, and Amazon forests comprise the dominant source to the global atmosphere. Still, there is a poor understanding of how isoprenoid emission capacities vary in response to ecophysiological and environmental controls in Amazonian ecosystems. We measured isoprenoid emission capacities of three Amazonian hyperdominant tree species – Protium hebetatum, Eschweilera grandiflora, Eschweilera coriacea – across seasons and along a topographic and edaphic environmental gradient in the central Amazon. From wet to dry season, both photosynthesis and isoprene emission capacities strongly declined, while emissions increased among the heavier isoprenoids: monoterpenes and sesquiterpenes. Plasticity across habitats was most evident in P. hebetatum, which emitted sesquiterpenes only in the dry season, at rates that significantly increased along the hydro‐topographic gradient from white sands (shallow root water access) to uplands (deep water table). We suggest that emission composition shifts are part of a plastic response to increasing abiotic stress ( e.g . heat and drought) and reduced photosynthetic supply of substrates for isoprenoid synthesis. Our comprehensive measurements suggest that more emphasis should be placed on other isoprenoids, besides isoprene, in the context of abiotic stress responses. Shifting emission compositions have implications for atmospheric responses because of the strong variation in reactivity among isoprenoid compounds. Abstract : Amazonian tree species emit less isoprene but more heavier isoprenoids in response to abiotic stress, such as heat and drought.